الفهم القرائي لدى تلاميذ السنة الخامسة ابتدائي في ضوء متغيري - بن نذير, الزهرة; حجاج, عمر (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى التعرف على مهارات الفهم القرائي لدى تلاميذ السنة الخامسة ابتدائي في ضوء متغيري (نوع القراءة والنص المقروء)، باستخدام المنهج الوصفي، وتمثلت أدوات الدراسة في قائمة لمهارات الفهم القرائي واختبار لمهارات الفهم، وبعد التأكد من صدقها وثباتها طُبقت على عينة تكونت من (180) تلميذا من تلاميذ السنة الخامسة بمدينة متليلي، وتوصلت النتائج إلى: وجود فروق ذات دلالة إحصائية في مهارات الفهم القرائي لدى تلاميذ السنة الخامسة ابتدائي تعزى لنوع القراءة لصالح القراءة الجهرية، ولنوع النص المقروء لصالح النص الأدبي، ولمستويات الفهم القرائي لصالح المستوى الحرفي، يليه المستوى الاستنتاجي فالمستوى النقدي، تم المستوى التذوقي وأخيرا المستوى الإبداعي. Abstract: This study aimed to identify reading comprehension skills of the fifth year in primary school in terms of the tow variables (Reading type and text read), using the descriptive approach, and the study tools consisted of a list of reading comprehension skills and a test of those skills, and after verifying its validity and reliability, it was applied on a sample consisting of (180) fifth year students in the city of Metlili. the results revealed: There are statistically significant differences in those pupils reading comprehension skills due to the type of reading in favor of aloud reading, and the type of text read in favor of the literary text, and to the reading comprehension in favor of the literal level, followed by the deductive, the critical, the tasting, and finally creative level.
نوع القراءة والنص المقروء
مقال
Keywords: الفهم القرائي ; نوع القراءة ; نوع النص المقروء